Association of Chronic Periodontitis with Reduced Haemoglobin Level - Ranjit, Rebicca; Acharya, Pujan; Baniya, Bikash Kumar; Adhikari, Khushbu (Journal of Nepalese Society of Periodontology and Oral Implantology, 2022)
Introduction: Chronic periodontitis is an infectious disease of supporting tissues of tooth due to subgingival colonisation of pathogenic bacteria. Microorganisms or their by-products can invade periodontal tissues through ulcerated pocket epithelium and gain access to systemic circulation producing proinflammatory cytokines which can downregulate erythropoiesis in bone marrow thereby decreasing blood counts. Conversely, reduced oxygen-carrying capacity of blood in anaemic patients cause impaired oxygen supply to periodontal tissues leading to persistent pathogenic bacterial challenge. Objective: To observe the association of chronic periodontitis with reduced level of haemoglobin. Methods: This case-control study was conducted from 2015 May to 2016 May at UCMS after ethical approval. Sixty systemically healthy patients (controls=30 with healthy periodontium; cases=30 with chronic periodontitis) visiting Department of Periodontology and Oral Implantology, were included in study. The clinical parameters (gingival index, probing pocket depth, clinical attachment loss) and serum haemoglobin level of the participants were compared. Statistical analysis using student’s unpaired t-test, analysis of variance, Pearson’s correlation and Odd’s ratio was performed. Results: Statistically significant difference between cases and controls in haemoglobin level (11.64±1.489 g/dl and 12.85±1.360 g/dl respectively) was observed. The correlation analysis showed statistically moderate negative correlation of haemoglobin concentration with pocket depth (r=-0.424) and weak negative correlation with clinical attachment level (r=-0.307). Conclusions: Chronic periodontitis patients had lower haemoglobin level compared to healthy controls. This suggests that chronic periodontitis like, any other long-standing conditions, may be associated with risk for anaemia. As these chronic conditions reinforce each other, meticulous management of either may assist treatment of other.